Perceptions of Decision-Making in Western Australian Iron Ore Companies Dealing with Chinese Companies - Leong Yen-Yen Ralph, Renée (Curtin University, 2019)
Decision making in Western Australia’s iron ore companies dealing with Chinese companies is vital for long-term relationship. In-depth qualitative interviews with 31 participants at senior management and executive level provide “lived” insights and “multi-realities” of decision making. Significant differences exist in terms of decision frameworks: collective, individual and hierarchical. The data points to a guanxi concentric circles model and the nuances of contract. An Emergent Decision Making Model is proposed to improve decision making processes.